Prevalence of symptoms of depression and generalized anxiety disorder in field hockey players of German first and lower leagues - Junge, A.; Wellmann, K.; Zech, A. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background While several studies on mental health of elite athletes were published in recent years, few compared the prevalence with the general population and none included field hockey players.